Стан і тенденції розвитку виробництва холодної прокатки труб зі сплавів на основі титану - Міщенко, О.В. (Physico-technological Institute of Metals and Alloys, 2023)
Status and trends in the development of the production of cold-rolled pipes from titanium-based alloys are analyzed. The modern standards used at the enterprises in the production of cold-formed pipes from titanium alloys are given. In the course of analyses, a comparison of the two types of modern enterprises for the production of cold-deformed pipes from titanium alloys was made and an assumption was made about the trends of development of enterprises in the future. The regularities are revealed and the principles of development of manufacturing routes based on the features of pipes from titanium-based alloys are formulated. The influence of the main parameters of the technology on the production efficiency and quality of the finished pipe products is shown. The mode of cold pilger rolling tubes of titanium-based alloys is recommended that contribute to reducing the number of cyclic rolling, reducing the expenditure ratio of the metal, obtaining the required level of mechanical properties and receiving the required level the accuracy of the manufactured products. The issues of not only the accuracy of the pipes, but also the billet used in the manufacture of cold-rolled pipes from titanium alloys are considered. The features of the wall thickness variations for each type of billet used in enterprises are described. The recommendations on the depth of removal of the surface layer of scale between rolling are given. The influence of such parameters as divisibility of deformation, total reduction of the cross-section, move and rotation of a pipe in the rolling process, the choice a lubricant and method of its application on the pipe, the temperature at a deformation zone, the gas saturation of the surface and their influence on pipe accuracy are analyzed. Recommendations on these parameters are given to improve the quality of pipes made of titanium alloys with a description of the limitations caused by the characteristics of the alloys.